Identification of HOXD4 Mutations in Spinal Extradural Arachnoid Cyst. - Yoji Ogura; Noriko Miyake; Ikuyo Kou; Aritoshi Iida; Masahiro Nakajima; Kazuki Takeda; Shunsuke Fujibayashi; Masaaki Shiina; Eijiro Okada; Yoshiaki Toyama; Akio Iwanami; Ken Ishii; et al. (PLoS ONE, 2015)
Spinal extradural arachnoid cyst (SEDAC) is a cyst in the spinal canal that protrudes into the epidural space from a defect in the dura mater and leads to neurological disturbances. We previously showed that familial SEDAC is caused by FOXC2 mutation; however, the causal gene of sporadic SEDAC has not been identified. To identify the causal gene of sporadic SEDAC, we performed whole exome sequencing for 12 subjects with sporadic SEDAC and identified heterozygous HOXD4 loss-of-function mutations in three subjects. HOXD4 haplo-insufficiency causes SEDAC and a transcriptional network containing HOXD4 and FOXC2 is involved in the development of the dura mater and the etiology of SEDAC.